نسقية الكتابة وتشكيل المتخيل - عقاب, بلخير (Sciences humaines, 2014)
systematic of the writing and the forming of the imagination My these boils down to a search to determine the style of writing that go beyond the limits of the partial view of their work, while wearing his history in the system of words from previous periods, and understand them in the way of accessing the knowledge of their content, and then get the understanding, and correct interpretation of its terms. Moreover, writing it forms and requires its laws, and its conditions is deposited, it is expressed more in the social and cultural status thanks to lector, where it fits and starts in its presumed authority to added is determined, acculturated, have opinions all in activating new acts of writing. Thus, we find that the development and evolution of writing through the ages, it reaches this distinct understanding of levels of writing, and its mode expressions of his age, and also its interaction communities whose ideas and trends are different That's when it is activated in a way it has become a means of input and added, this has concerned various generations. (Creative text for best example of this). On the other hand, writing is a cumulative of humanitarian progress in its entirety, it is his experience and continued existence is beyond the historical facts, cycles and chronic, yet the historical reading is not aware of facts writing if it is caused by a vision that means, examines and adds.     يتلخص بحثي في تحديد نمط الكتابة التي تتجاوز حدود النظرة الآنية لعملها، وتنظر إليها نظرة أحادية، في حين أنها تحمل تاريخها وكلها داخل منظومة كلامية قادمة من عصور سابقة، وأما معالجاتها فتكمن في مستوى فهمها وكيفية الدخول إلى محتوياتها المعرفية، ومن ثم تحقيق شروط الفهم والتأويل الصحيح. هذا ناهيك أن الكتابة تشكل قوانينها وتبسط حدودها وتعبر عن نفسها ووجودها، داخل محيط ثقافي واجتماعي تعبر عنه وتنتظر قارئا يتفاعل معها ويرهن نفسها داخل سلطتها المفترضة،      من أجل إضافة وفهم ، ضبط حدود مثاقفة، وجهات نظر وتحفيز لفعل جديد من الكتابة. هكذا نجد أن التطور والتغيير الحاصل لمستوى الكتابة عبر العصور، جاء وفق هذا الفهم الدقيق لمستويات الكتابة وتعبيرها عن عصرها وتفاعلها داخل مجتمعات وأفكار متعددة المشارب والاتجاهات، ومن ثم تحفزت الكتابة لأن تظهر بشكل يربط الحلقات ويضيف عند أجيال مختلفة(النص الإبداعي كأحسن مثال على ذلك). ومن جهة أخرى الكتابة هي حاصل الجهد البشري في كليته، ومنه فهي المعبر المتجدد عنه بعكس التاريخ الذي يؤرخ لفعلها، لكنه ينحصر    في إطار زمني لا يتعداه، إلا إذا كان واعيا لقراءة نشطة وفاعلة تستخلص وتمحّص وتضيف